2017
DOI: 10.1136/bmjopen-2017-018587
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing studies for novel drugs approved by both the FDA and EMA between 2005 and 2010: a cross-sectional study

Abstract: ObjectivesTo characterise postmarketing studies for drugs that were newly approved by the US Food and Drug Administration and the European Medicines Agency.Design and settingCross-sectional analysis of postmarketing studies registered in ClinicalTrials.gov until September 2014 for all novel drugs approved by both regulators between 2005 and 2010. Regulatory documents from both agencies were used.Primary and secondary outcome measuresAll identified postmarketing studies were classified according to planned enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…There is high variability in the number of trials pursued per trajectory and also in the number of patients enrolled per trajectory. This confirms a result shown in other work conducted on postapproval trials in the same time period 26. This variability may arise from many different sources: lack of coordination, market considerations, regulatory incentives for rare diseases or individual agendas of small research centres.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…There is high variability in the number of trials pursued per trajectory and also in the number of patients enrolled per trajectory. This confirms a result shown in other work conducted on postapproval trials in the same time period 26. This variability may arise from many different sources: lack of coordination, market considerations, regulatory incentives for rare diseases or individual agendas of small research centres.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings might also inform research policy. Others have reported high levels of postapproval clinical testing and raised concerns about redundancy and the lack of coordination of postapproval trials 26. One study suggested a relationship between high revenue generation for a drug and postapproval testing 27.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 However, nearly one-quarter of clinical postmarketing requirements and commitments focused on modified or unapproved therapeutic indications, including one-half of confirmatory postmarketing requirements for therapeutics receiving accelerated approval designation. This rate is comparable to that observed for postmarket clinical studies overall, which are primarily sponsored by industry, 32 frequently evaluate new therapeutic uses, 33,34 and may play a role in promoting medication use after approval. 35 This has also been observed for therapeutics receiving accelerated approval designation, which are integrated into clinical practice, including new applications, without confirmation of clinical benefit for original indications.…”
Section: Discussionsupporting
confidence: 59%